1991
DOI: 10.1159/000120580
|View full text |Cite
|
Sign up to set email alerts
|

Continuous External Drainage in the Treatment of Subdural Hematomas of Infancy

Abstract: A series of 16 patients with chronic or subacute subdural hematomas treated with continuous external drainage of the subdural space is reviewed. Of these only 44% went on to require subdural-peritoneal shunt placement. There were no complications in treatment and no clinical or laboratory evidence of infection in any case. The outcome, measured by neurological examination, was not different between the shunted and nonshunted groups. In conclusion, continuous external drainage of the subdural space in chronic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 1 publication
(1 reference statement)
0
21
0
Order By: Relevance
“…2,8,16 Nevertheless, drainage must be maintained for a long period (median 6-15 days), with hospitalization in the intensive care unit and hydro-electrolytic compensation; therefore, the economic cost is high and must be taken into account along with the actual economic context. Some authors still advocate the use of minicraniotomy given its good success rate, but this method is quite invasive.…”
Section: Discussionmentioning
confidence: 99%
“…2,8,16 Nevertheless, drainage must be maintained for a long period (median 6-15 days), with hospitalization in the intensive care unit and hydro-electrolytic compensation; therefore, the economic cost is high and must be taken into account along with the actual economic context. Some authors still advocate the use of minicraniotomy given its good success rate, but this method is quite invasive.…”
Section: Discussionmentioning
confidence: 99%
“…While Ingram and Matson [8] had recommended craniotomy for evacuation of the hemato ma, removal of membranes, and a reduction cranioplasty to minimize the craniocerebral disproportion, the trend in recent years has been towards more conservative ap proaches such as subdural tapping [9,10], continuous external drainage [11], and subduroperitoneal shunting [12,13], The decision to perform a subduroperitoneal shunt in this patient was based on our impression that the collection of this size with multicompartmental extent was unlikely to resolve with repeated tappings. A recent study of 103 pediatric patients with subdural collections suggested that eventually 70% of the patients on whom subdural taps or continuous external drainage had been attempted end up requiring a subduroperitoneal shunt [13].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of 103 pediatric patients with subdural collections suggested that eventually 70% of the patients on whom subdural taps or continuous external drainage had been attempted end up requiring a subduroperitoneal shunt [13]. Even in the series recommending tapping [10] or external drainage [11] as the first procedure, more than 40-50% of the patients had eventually required a shunt.…”
Section: Discussionmentioning
confidence: 99%
“…Failure rates vary widely, from 6% to 48%, with one paper reporting an infection rate of 8%. 4,7,9,16,17,27 Bur hole evacuation is slightly more invasive but is also straightforward. It requires general anesthesia and allows the surgeon to irrigate the subdural space and leave a drain in place if necessary; however, it still has the disadvantage of limited exposure and thus a relative inability to deal adequately with loculated collections.…”
mentioning
confidence: 99%